The Effect of Content Quality on the @Tanyakanrl Account on Followers' Interest in Responding on the X App - Cindoswari, Ageng Rara; Cendani, Ayanda Zahwa Sekar (Petra Christian University, 2026)
This study aims to analyze the effect of content quality on followers’ interest in replying (behavioral intention) to posts on the @tanyakanrl account on the X app. This study employs a quantitative approach using a correlation method. The population for this study consists of 3,204,423 followers of the @tanyakanrl account, with a sample of 100 respondents determined using the Slovin formula. Data were collected via a questionnaire using a Likert scale and analyzed using simple linear regression with SPSS version 26. The results indicate that content quality has a positive and significant influence on followers’ interest in replying, with a p-value of 0.004 (<0.05). The coefficient of determination (R²) was 0.436, indicating that content quality accounts for 43.6% of the variation in followers’ interest in replying, while the remaining 56.4% is influenced by other factors outside the model. These findings suggest that higher content quality—measured through aspects of relevance, presentation, language, and design—can increase followers’ interest (intent, prediction, and willingness) to actively engage through replies. This study contributes to the development of digital communication research by highlighting the role of content quality as a primary determinant of active engagement on social media platforms.